Studies on Structural, Dielectric and Piezoelectric Properties of Doped PCT Ceramics - Sharma, Mohit (My University, 2007)
Ceramics have traditionally admired for their mechanical and thermal stability, their unique electrical, optical and magnetic properties. These features make ceramics important in many key technologies including communication, energy conversion and storage, electronics and automation. Electroceramics are the advance structural ceramics materials used for electronic applications. Developments in these materials are categorized as smart materials, have paralleled the growth of new technologies. Example includes Ferroelectrics – high dielectric constant, non-volatile memories; Ferrites – data and information storage; Solid electrolytes, energy storage and conversion; Piezoelectrics – sensors, actuators, transducers, sonar etc. Lead titanate (PT) ceramics are very promising piezoelectric materials for high temperature and high frequency applications because of their high curie temperature and low dielectric constant. Pure lead titanate ceramics are difficult to sinter because of their large anisotropy. On cooling through the curie temperature, the large anisotropy cause the ceramics to become fragile. By addition of small amount of suitable additives, cracking can be prevented. In the present work, the effect of lanthanum substitutions on the structural, dielectric and piezoelectric properties of lead calcium titanate (PCT) ceramics going to be investigate. The sample with composition formula Pb0.76-x/2LaxCa0.24 (Ti0.98Mn0.02) 1-x/2O3 and Pb0.76Ca0.24Mn0.02Ti 0.98-5x/4TaxO3, with x = 0 - 0.02 prepared by solid state reaction method. Structural and phase analysis carried out by SEM and XRD. Dielectric and piezoelectric parameters study helps to show that La3+, Ta5+ substitution improves the electromehanical properties of lead calcium titanate.
Keywords: PCT Ceramics; Dielectric; Poling; Lead Titanate Ceramics; Piezoelectric Properties